AlNbBr8 – Preparation, Crystal Structure, and Vapor Pressure Studies. Issue 14 (6th July 2016) - Rogachev, Alexander V.; Zelenina, Ludmila N.; Chusova, Tamara P.; Virovets, Alexander V.; Sokolov, Maxim N.
Abstract: The ternary niobium compound AlNbBr8 (1 ) was synthesized by degradation of NbS2 Br2 in AlBr3 and from elements. Crystal structure and thermodynamic properties of sublimation process were studied. Abstract :